Corruption Crimes Committed by the Former Regent of Hulu Sungai Tengah - Saqinah, Nabilla Salsa; Alhadi, Muhammad Nurcholis; Rahayuningsih, Uut (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: This study examines the case of the former Regent of Hulu Sungai Tengah, Abdul Latif, who has been proven guilty of corruption and money laundering in Decision Number 12/PID.SUS-TPK/2023/PT BJM.Purposes of the Research: The purpose of this study is to analyze whether the criminal elements contained in Decision Number 12/PID.SUS-TPK/2023/PT BJM have been proven in their entirety and what kind of punishment was imposed by the panel of judges.Methods of the Research: This study uses a normative juridical method with a case study approach and legislative analysis.Findings of the Research: This investigation found that all elements of the crime had been proven legally guilty based on evidence, witness testimony, and trial facts. However, the prison sentence and obligation to pay compensation imposed were still not proportional to the amount of state losses, which amounted to IDR.41,553,554,006.00.